(untitled) (Journal of Student Affairs in Africa, 2012)
Higher education in South Africa has focused extensively on widening access to further inclusivity and to economic development. However, as students need to persist and succeed in their studies, access alone is not enough. Furthermore, the responsibility of higher education to help students succeed does not end with graduation; institutions need to produce graduates who are ready to enter the labour market. Therefore, it is important to integrate career information and concepts into these practices when conceptualising holistic academic advising. Since academic advising is still developing as a professional practice in the South African context, no clear, practical framework has been used uniformly at universities. Career advice is also not necessarily integrated into academic advising in a conscious manner. This may result in students who are struggling to integrate all the academic and career information provided to make informed decisions regarding their studies and career paths. This paper argues that the 3-I Process is an appropriate framework for the integration of career and academic advising in the South African context. In this case study, we draw from the experiences of nine advisors from the central advising office, faculties, and the career office at the University of the Free State to understand the extent to which they have been incorporating the elements of the 3-I Process into their existing academic advising practices and how they view the possibilities of following a more integrated approach. We also map how the framework can be adapted to the broader South African context to inform and develop more holistic and professionalised advising practices, as well as to contribute towards students’ success beyond university.